Implementasi Nilai-Nilai Panca Cinta dalam Kurikulum Berbasis Cinta dalam pendidikan karakter di Raudhatul Athfal Kota Pekanbaru - Roby Seprya (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study aims to analyze the implementation of the Panca Cinta values within the Love-Based Curriculum (Kurikulum Berbasis Cinta/KBC) in Raudhatul Athfal (RA) in Pekanbaru City. This study employed a descriptive qualitative approach involving RA principals and teachers as primary informants and madrasa supervisors as supporting informants. Data were collected through observation, semi-structured interviews, and documentation, and analyzed using the interactive model of data condensation, data display, and conclusion drawing. The findings indicate that the implementation of Panca Cinta is integrated into daily learning activities, habituation, teacher modeling, social interaction, and the educational environment. The five dimensions love for Allah and His Messenger, love of knowledge, love for the environment, love for oneself and others, and love for the homeland are implemented through prayer and religious habituation, exploratory and play-based learning, environmental care, sharing and cooperation, and the introduction of national and local cultural values. Teacher role modeling and habituation are the main mechanisms for internalizing these values. The findings are consistent with humanistic theory, particularly the importance of acceptance, empathy, and supportive relationships, as well as Bandura's social learning theory concerning observation and behavioral modeling. This study contributes an integrative perspective on character education by demonstrating that Panca Cinta can connect spiritual, intellectual, social-emotional, ecological, and national values within early childhood Islamic education